EFFECT OF Plant Growth Promoting Rizhobacteria DOSAGE OF Pannisetum purpureum ROOTS AND VARIOUS WATER CONTENT ON PRODUKTIVITY OF Clitoria ternatea - T. P. A., Ahmad; Duarsa, M. A. P.; Lindawati, S. A. (Jurnal Peternakan Tropika, 2024)
The study aimed to determine the effect of Plant Growth Promoting Rhizobacteria doses of Pennisetum purpureum roots and different water content on the productivity of Clitoria 298 ternatea. The research was conducted in the greenhouse of Sading Village, Mengwi District, Badung Regency The study lasted for two months, using a completely randomized design in a factorial pattern consisting of 2 factors consisting of 3 levels of PGPR dosage (D0 = 0ml/pot, D10 = 10ml/pot and D20 = 20ml/pot) and 3 levels of moisture content (K25 = 25%KL, K50 = K50%KL and 100% field capacity).There were 9 treatment combinations and each treatment had 4 replications, so there were 36 experimental units. The variables observed were growth variables, yield variables and growth characteristic variables. The results showed no interaction between the dose of PGPR Pennisetum purpureum root and various water levels on all variables. The dose factor of PGPR Pennisetum purpureum root showed the highest results at a dose of 20ml/pot of water on Clitoria ternatea productivity. Water content tends to show the highest results in the provision of 100% field capacity of Clitoria ternatea plant productivity. From the results of the study it can be concluded that there is no interaction between the dose of PGPR Pennisetum purpureum roots and various water levels on all variables (growth, yield and growing characteristics), The treatment of PGPR dose of pennisetum purpureum root 20ml/pot and 100% water content gave the best response in affecting the productivity of Clitoria ternatea.